Secondary metabolites from Sambueus ebulus - Atay, Irem; Kirmizibekmez, Hasan; Goren, AHMET CEYHAN; GÖREN, AHMET CEYHAN; Yesilada, Erdem (My University, 2015)
A new nonglycosidic iridoid, sambulin B (1), was isolated from the methanol extract of Sambucus ebulus L. leaves along with a recently reported new nonglycosidic iridoid, 10-O-acetylpatrinoside aglycone (sambulin A) (2); 2 flavonoids, isorhamnetin-3-O-beta-D-glucopyranoside (3) and isorhamnetin-3-O-rutinoside (4); and a mixture of 2 flavonoids (5), quercetin-3-O-beta-D-glucopyranoside and quercetin-3-O-beta-D-galactopyranoside. Their structures were elucidated by 1-D and 2-D nuclear magnetic resonance spectroscopy (NMR) and mass spectrometry (MS) experiments.